Subnormothermic Ex Vivo Porcine Kidney Perfusion Improves Energy Metabolism: Analysis Using 31P Magnetic Resonance Spectroscopic Imaging. Issue 10 (26th September 2022) - Agius, Thomas; Songeon, Julien; Klauser, Antoine; Allagnat, Florent; Longchamp, Grégoire; Ruttimann, Raphael; Lyon, Arnaud; Ivaniesevic, Julijana; Meier, Raphael; Déglise, Sébastien; Markmann, James F.; Uygun, Korkut; et al.
Abstract : Background: The ideal preservation temperature for donation after circulatory death kidney grafts is unknown. We investigated whether subnormothermic (22 °C) ex vivo kidney machine perfusion could improve kidney metabolism and reduce ischemia-reperfusion injury. Methods: To mimic donation after circulatory death procurement, kidneys from 45-kg pigs underwent 60 min of warm ischemia. Kidneys were then perfused ex vivo for 4 h with Belzer machine perfusion solution UW at 22 °C or at 4 °C before transplantation. Magnetic resonance spectroscopic imaging coupled with LCModel fitting was used to assess energy metabolites. Kidney perfusion was evaluated with dynamic-contrast enhanced MRI. Renal biopsies were collected at various time points for histopathologic analysis. Results: Total adenosine triphosphate content was 4 times higher during ex vivo perfusion at 22 °C than at 4 °C perfusion. At 22 °C, adenosine triphosphate levels increased during the first hours of perfusion but declined afterward. Similarly, phosphomonoesters, containing adenosine monophosphate, were increased at 22 °C and then slowly consumed over time. Compared with 4 °C, ex vivo perfusion at 22 °C improved cortical and medullary perfusion. Finally, kidney perfusion at 22 °C reduced histological lesions after transplantation (injury score: 22 °C: 10.5 ± 3.5; 4 °C: 18 ± 2.25 over 30). Conclusions: Ex vivo kidney perfusion at 22°C improved graft metabolism and protected from ischemia-reperfusion injuries upon transplantation. Future clinical studies will need to define the benefits of subnormothermic perfusion in improving kidney graft function and patient's survival.